Tata Kelola Syariah: Peran Vital Dewan Pengawas Syariah dalam Mewujudkan Kepatuhan dan Kinerja Bank Syariah - Firmansyah, Amrie; Hidayat, Fikri (Universitas Muhammadiyah Prof. DR. HAMKA, 2024)
This study aims to analyze the role of the Sharia Supervisory Board (DPS) in the governance of Islamic banks in Indonesia, with a focus on the supervision of sharia compliance and its influence on financial performance. The method used is scoping review, by collecting and analyzing 33 relevant articles that discuss the functions and challenges of DPS. The results of the study show that DPS has a central role in ensuring compliance with sharia principles and contributing positively to the financial performance of Islamic banks. The competence of DPS members, including the size and frequency of meetings, has been proven to affect the effectiveness of supervision. Nonetheless, DPS face challenges, such as a lack of qualified human resources and adequate education, which can reduce the effectiveness of their supervision. The study also found that DPS functions as a moderator in the relationship between the board of directors and bank performance, strengthening Good Corporate Governance (GCG) in Islamic banks. Thus, it is important for the Financial Services Authority (OJK) to improve the competence of DPS through stricter training programs and regulations. This research provides significant insights for policy development in the Islamic banking sector, with the hope of improving the credibility and performance of Islamic banks in Indonesia